Erssonite, CaMg7Fe3+2(OH)18(SO4)2⋅12H2O, a new hydrotalcite-supergroup mineral from Långban, Sweden. (2nd October 2021) - Zhitova, Elena S.; Chukanov, Nikita V.; Jonsson, Erik; Pekov, Igor V.; Belakovskiy, Dmitry I.; Vigasina, Marina F.; Zubkova, Natalia V.; Van, Konstantin V.; Britvin, Sergey N.
Abstract: The new wermlandite-group mineral erssonite, ideally CaMg7 Fe 3+ 2 (OH)18 (SO4 )2 ⋅12H2 O (or [Mg7 Fe 3+ 2 (OH)18 ][Ca(SO4 )2 ]⋅12H2 O), was discovered in a late-stage, low-temperature assemblage in cavities of a magnetite-bearing dolomitic rock from the Långban deposit, Värmland county, Bergslagen ore province, Sweden. The associated minerals are dolomite, calcite, members of the magnetite–magnesioferrite solid-solution series, phlogopite, chrysotile, pyroaurite and norbergite. Erssonite has a vitreous lustre and forms colourless, platy hexagonal crystals flattened on [0001], up to 0.5 mm across and up to 10 μm thick, occurring mainly as aggregates in cavities of dolomitic rock. Erssonite is malleable; separate crystals are flexible and non-elastic, with a perfect, mica-like cleavage on {0001}. The calculated density is equal to 2.02 g⋅cm –3 . Raman spectroscopy shows the presence of typical bands for S–O bonds attributed to intercalated SO4 2– anions and structural OH – anions together with the absence of C–O bonds, attributed to carbonate anions. The chemical composition is (wt.%, electron microprobe, H2 O content is calculated from structure data): MgO 28.67, CaO 2.76, Al2 O3 0.23, Cr2 O3 0.23, Fe2 O3 16.00, SiO2 0.48, SO3 14.80, H2 O 35.58, total 98.75. The empirical formula based on 38 O atoms is H41.48 Ca0.52 Mg7.47 Fe 3+ 2.11 Al0.05 Cr0.03 S1.94 Si0.08 O38 . The ideal formula is CaMg7 Fe 3+ 2 (OH)18 (SO4 )2 ⋅12H2 O or {Mg7 Fe 3+ 2 (OH)18 }{[Ca(H2 O)6 ](SO4 )2 (H2 O)6 }. The crystal structure was determined using single-crystal X-ray diffraction data and refined to R = 0.093. Erssonite is trigonal, P $\bar{3}$ c 1, with a = 9.3550(6), c = 22.5462(14) Å, V = 1708.8(2) Å 3 and Z = 2. The strongest lines of the powder X-ray diffraction pattern [ d, Å ( I, %)( hkl )] are: 11.22 (90)(002), 5.63 (64)(004), 4.670 (100)(110, 104, 014), 2.626 (64)(032, 302), 2.435 (66)(034, 304) and 1.951 (45)(038, 308). The mineral is named in honour of the Swedish amateur mineralogist Dr. Anders Ersson (b. 1971).